Transformasi Digital UMKM melalui Pemanfaatan Artificial Intelligence dalam Meningkatkan Daya Saing Bisnis di Era Ekonomi Digital - Erwin Maulana Abdul Kadir; Eddy Soeryanto Soegoto; Rahma Wahdiniwaty; Irfan Dwiguna Sumitra (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in the national economy; however, they continue to face various challenges in enhancing their competitiveness in the digital economy era. Technological advancements, particularly Artificial Intelligence (AI), create new opportunities for MSMEs to undertake digital transformation in a more effective and sustainable manner. This study aims to analyze the role of Artificial Intelligence utilization in supporting the digital transformation of MSMEs and its impact on improving business competitiveness.This research employs an approach tailored to the characteristics of MSMEs, with data collected from MSME actors who have begun adopting digital technologies in their business activities. The results indicate that the utilization of Artificial Intelligence contributes to improved operational efficiency, higher-quality decision-making, and enhanced capability of MSMEs to respond to market needs more quickly and accurately. Furthermore, AI encourages business model innovation and strengthens the competitive position of MSMEs amid digital economic competition. The study concludes that Artificial Intelligence can serve as a key strategy in the digital transformation of MSMEs to sustainably enhance business competitiveness.